White Box Testing with Path Testing on the Web-Based Population and Civil Registration Service (Dukcapil) Submission Status Notification Module in Kuningan Barat Subdistrict - Dimas Abimanyu Panji; safrizal safrizal (Journal of Applied Research In Computer Science and Information Systems, 2025)
Software testing is a stage in ensuring the quality and reliability of the system before it is implemented operationally. This study aims to evaluate the accuracy of the program logic flow in the web-based DUKCAPIL service submission status notification module in Kuningan Barat Village using the white box testing method with a path testing approach. This method is to analyze the internal structure of the program code to ensure that all logic paths have been thoroughly tested. The testing process begins with the identification of the path basis using the control flow (Control Flow Graph), calculation of cyclomatic complexity, and determination of the test path set. The test results show that all logic paths in the notification module have been passed and no logical errors were found in the program flow. Thus, this module is declared to have met the eligibility criteria in terms of internal logic. This study is expected to be a reference in improving the quality of testing web-based public service information systems, especially in terms of the reliability of population administration service notifications.